2017
DOI: 10.1080/02615479.2017.1406467
|View full text |Cite
|
Sign up to set email alerts
|

Preparing social workers for practice with LGBT populations affected by substance use: perceptions from students, alumni, and service providers

Abstract: Trends in the field of service among those with alcohol and other drug addictions highlight the urgent need for schools of social work to effectively train students to serve clients with substance use disorders, as well as to have cultural competence to effectively serve disproportionately affected and historically underserved lesbian, gay, bisexual, transgender (LGBT) consumers. Online surveys and interviews examined graduate social work (MSW)/certified alcohol and drug counselor (CADC) student preparedness t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…However, we noticed education approaches of other professions such as pharmacy, social work, or physician assistants. The subject of culturally competent and gender-affirmative care concerns a wide range of disciplines, and evidence proves a lack of preparedness and knowledge about unique needs and problems of transgender clients across many professions [80][81][82][83][84][85]. Therefore, a positive aspect to highlight is the effort of three authors to design an IPE activity by using case discussion in groups [54], video discussions [55] or standardised patient simulations [53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we noticed education approaches of other professions such as pharmacy, social work, or physician assistants. The subject of culturally competent and gender-affirmative care concerns a wide range of disciplines, and evidence proves a lack of preparedness and knowledge about unique needs and problems of transgender clients across many professions [80][81][82][83][84][85]. Therefore, a positive aspect to highlight is the effort of three authors to design an IPE activity by using case discussion in groups [54], video discussions [55] or standardised patient simulations [53].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the number of hours dedicated to LGBTQI health is highly variable [81,92,94] but has a major influence on students' preparedness, attitudes, and knowledge along with the exposure to LGBT clients [81]. But as several studies identified providers have lower knowledge and feel more discomfort when caring for transgender individuals compared to LGB people [84,[95][96][97] it may be wise to discuss the subject separately. This is in line with the results of Tyler et al [56] who described their students performed significantly worse in a scenario with a transgender client than with a bisexual client.…”
Section: Discussionmentioning
confidence: 99%